EFFECTIVENESS OF CONTINUOUS AUTOMATIC BLADDER IRRIGATION BASED ON INTERNET OF THINGS IN TRANS URETHRAL RESECTION OF PROSTATE: ANALYSIS OF NURSES’ KNOWLEDGE AND READINESS - Bekti Setiawan; Joko Prasetyo; Novita Ana Anggraini (International Journal of Medical Science and Public Health Research, 2024)
Transurethral Resection of the Prostate (TURP) is a minimally invasive surgical procedure commonly performed to treat benign prostatic hyperplasia. However, complications such as TURP Syndrome can occur if the procedure is not performed correctly. Continuous Automatic Bladder Irrigation (CABI) based on the Internet of Things (IoT) is a technology developed to minimize the risk of these complications. This study aims to analyze the relationship between the knowledge and readiness of nurses in implementing IoT-based CABI on TURP complications at the Jombang Regional General Hospital. Quantitative methods were used in this study, including data collection techniques through observation and questionnaires. The results showed that nurse readiness significantly affected the effectiveness of CABI implementation and decreased TURP complications. The implications of this study indicate the importance of training and education for nurses in using IoT-based technology.